Resistive switching in ferromagnetic La2/3Ca1/3MnO3 thin films - Alposta, Ignacio; Kalstein, Ariel; Ghenzi, Néstor; Bengió, Silvina; Zampieri, Guillermo Enrique; Rubi, Diego; Levy, Pablo Eduardo (Institute of Electrical and Electronics Engineers, 2013)
Fil: Alposta, Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina